Sustainable indoor air purification using treated puffed rice waste: a functional and structural material evaluation - Dar Saleh, Abeer; Khoukhi, Maatouk; Mohammad, Ameera; Al Marzouqi, Ali; Bessadok-Jemai, Abdelbasset (Frontiers in Built Environment, 2025)
IntroductionThe study addresses IAQ and rice waste management with a bio-based material for CO₂ capture.MethodsRice was thermally puffed and treated with NaOH. Characterization and performance evaluation were conducted.ResultsAchieved 38% CO₂ removal at 2 M NaOH treatment, with enhanced porosity confirmed.DiscussionThe material provides a sustainable IAQ solution, suitable for architectural integration.